If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -3(x + -1) = 2x Reorder the terms: 7 + -3(-1 + x) = 2x 7 + (-1 * -3 + x * -3) = 2x 7 + (3 + -3x) = 2x Combine like terms: 7 + 3 = 10 10 + -3x = 2x Solving 10 + -3x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 10 + -3x + -2x = 2x + -2x Combine like terms: -3x + -2x = -5x 10 + -5x = 2x + -2x Combine like terms: 2x + -2x = 0 10 + -5x = 0 Add '-10' to each side of the equation. 10 + -10 + -5x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -5x = 0 + -10 -5x = 0 + -10 Combine like terms: 0 + -10 = -10 -5x = -10 Divide each side by '-5'. x = 2 Simplifying x = 2
| an=-6n+10 | | x+1/2=0.98 | | -16t^2+20t+4=0 | | z/10-4=10 | | -1/X=0 | | a^2+21a-540=0 | | (45x+54y)+(-2x+33y)= | | 4x-2/2=-3 | | -u/12=12 | | -7+|-5|= | | x-0.08x=1700 | | 18+6x-12=-8-4x+9x | | (9x^(1/2))^2 | | 14z-7/7 | | 2*B+3*A=5 | | (14x-27y)+(32x+65y)= | | 5/6x^2*3/6x^2 | | 3(x-4)=12x-4-9x | | 2x^3-15x^2+24x+12=0 | | (50x-8y)+(32x+37y)= | | 24+x=-18 | | -3x^2-12x+1=0 | | 28=w(2w-1) | | (x-2)(x+4)=14 | | x^2+x-36= | | 12c+5=c+31 | | 35x+-14=36x+-6 | | -18=x+20 | | 36x-14=36x-6 | | -22=11(2c-8) | | |-14|= | | (22-18)x(3+8)= |